The effect of POC and Pruning on the Growth and Production of Okra (Abelmoschous esculentus). - Al Machfudz WDP; Ahmad Basori (Nabatia, 2019)
This study aims to find effect of POC and pruning on the growth and production of okra (Abelmoschous esculentus). This research was conducted in Tulangan, Sidoarjo from December 2018 until March 2019. Research design used Randomized Block Design (RAK) with two factors. The first factor POC was P1 (1 ml/L), P2 (2 ml/L), and P3 (3 ml/L), second factor was pruning of branch C0 (without pruning), C1 (1x pruning), and C2 (2x pruning). The data obtained where then analyzed using ANOVA followed by BNJ 5%. The result showed there was significant interaction between POC and pruning on total dryed weight of plant and harvest index of okra. POC was significant effected on the all parameters of growth and production of okra. Pruning of branches was significant effect of talled of the plant and total of leaves. The best treatment was POC 3 ml/L and 1x pruning had plant lenght 47,44 cm, number of leaves 12,65 strands, rods diameters 1,04 cm, number of fruit 18,31, wet weight fruit 9,08 ton/ha, dry weight fruit 3,03 ton/ha and harvest index 0,79.